Analytical modeling and numerical analysis of the effect of mosaic patterns on composite pressure vessels with dome. (September 2021) - Akhtar, Muhammad Kaleem; Qureshi, Waqar Ahmad; Jamshed, Rehan; Raza, Mohsin
The aim of this work is to provide an analytical tool and numerical analysis for the optimum design of composite pressure vessels with the dome, incorporating triangular mosaic patterns. This article presents the analytical modeling involving kinematic constraints based on geodesic trajectory: the helical angle and dome thickness. The structural analysis is performed using a commercial finite element analysis tool. The results show that this new analytical method gives more accurate dome thickness than cubic spline function and Gramoll and Namiki's methods. The incorporation of mosaic patterns based on winding kinematics provides more realistic modeling of the real stress distribution and the stress values compared to the vessel without mosaic patterns and vessels with mosaic patterns based on nongeodesic trajectories. The results have been validated and are quite promising with regard to better accuracy and safety.